An investigation into mental illness and its comorbidities from the perspective of supervenience physicalism - Ping Yang; Xinyue Zhang; Hongwen Song; Xiaochu Zhang (Philosophy, Ethics, and Humanities in Medicine)
Abstract The exploration into the origin of human spirituality has always been a hot spot with many unsolved questions in the philosophy of mind, and issues concerning mental illness and its comorbidities are still unclear. In the 1970s, Donald Davidson first proposed anomalous monism with the supervenience concept, a theory that both insists on physicalism and transcends traditional reductionism. This theory provides solid and accessible proof for perceiving the mind-body relationship of spiritual origin in a non-reductionist approach. This paper develops arguments in two aspects. First, three principles of anomalous monism are employed to explore the origin of mental illness. Second, the comorbidity of mental illness is explained with the help of the supervenience theory.